2009
DOI: 10.1038/nchembio.217
|View full text |Cite
|
Sign up to set email alerts
|

Conformational inhibition of the hepatitis C virus internal ribosome entry site RNA

Abstract: The internal ribosome entry site (IRES), a highly conserved structured element of the hepatitis C virus genomic RNA, is an attractive target for antiviral drugs. Here we show that benzimidazole inhibitors of the HCV replicon act by conformational induction of a widened interhelical angle in the IRES subdomain IIa which facilitates the undocking of subdomain IIb from the ribosome and ultimately leads to inhibition of IRES-driven translation in HCV-infected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
215
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(223 citation statements)
references
References 18 publications
7
215
0
1
Order By: Relevance
“…4). 150 The benzimidazole was shown to induce a conformational change in the target RNA by interhelical widening of the IRES subdomain IIa. This causes a breakdown of the critical interaction of the IRES with the host cell ribosomes that leads to an inhibition of translation of the HCV polyprotein.…”
Section: Screeningmentioning
confidence: 99%
“…4). 150 The benzimidazole was shown to induce a conformational change in the target RNA by interhelical widening of the IRES subdomain IIa. This causes a breakdown of the critical interaction of the IRES with the host cell ribosomes that leads to an inhibition of translation of the HCV polyprotein.…”
Section: Screeningmentioning
confidence: 99%
“…The key to achieving a better therapeutic window relies on the feasibility of modifying the compound to preferentially inhibit viral translation. In a recent HCV study, benzimidazole compounds were shown to selectively bind and induce a conformational change of viral internal ribosome entry site (IRES) RNA, which weakens the ribosome docking and ultimately leads to inhibition of IRES-driven translation in HCV (28).…”
mentioning
confidence: 99%
“…1 A and B). The domain IIa, which is a potential target of antiviral drugs that block HCV protein synthesis (16), adopts a sharply bent fold that is required for the correct spatial positioning of the HCV IRES during recruitment of host cell ribosomes (17,18). Structural analysis of the unique 90°bend in the IIa domain led us to conclude that this viral RNA motif may constitute the most compact L-shaped object, or nanocorner, that can be built from contiguous double-stranded RNA.…”
Section: Resultsmentioning
confidence: 99%